Short-Term Repeatability of Noninvasive Aortic Pulse Wave Velocity Assessment: Comparison Between Methods and Devices. (20th October 2017) - Grillo, Andrea; Parati, Gianfranco; Rovina, Matteo; Moretti, Francesco; Salvi, Lucia; Gao, Lan; Baldi, Corrado; Sorropago, Giovanni; Faini, Andrea; Millasseau, Sandrine C; Scalise, Filippo; Carretta, Renzo; et al.
Abstract: BACKGROUND: Aortic pulse wave velocity (PWV) is an indirect index of arterial stiffness and an independent cardiovascular risk factor. Consistency of PWV assessment over time is thus an essential feature for its clinical application. However, studies providing a comparative estimate of the reproducibility of PWV across different noninvasive devices are lacking, especially in the elderly and in individuals at high cardiovascular risk. METHODS: Aimed at filling this gap, short-term repeatability of PWV, estimated with 6 different devices (Complior Analyse, PulsePen-ETT, PulsePen-ET, SphygmoCor Px/Vx, BPLab, and Mobil-O-Graph), was evaluated in 102 high cardiovascular risk patients hospitalized for suspected coronary artery disease (72 males, 65 ± 13 years). PWV was measured in a single session twice, at 15-minute interval, and its reproducibility was assessed though coefficient of variation (CV), coefficient of repeatability, and intraclass correlation coefficient. RESULTS: The CV of PWV, measured with any of these devices, was <10%. Repeatability was higher with cuff-based methods (BPLab: CV = 5.5% and Mobil-O-Graph: CV = 3.4%) than with devices measuring carotid-femoral PWV (Complior: CV = 8.2%; PulsePen-TT: CV = 8.0%; PulsePen-ETT: CV = 5.8%; and SphygmoCor: CV = 9.5%). In the latter group, PWV repeatability was lower in subjects with higher carotid-femoral PWV. The differences in PWV between repeated measurements, except for the Mobil-O-Graph, did not depend on short-term variations of mean blood pressure or heart rate. CONCLUSIONS: Our study shows that the short-term repeatability of PWV measures is good but not homogenous across different devices and at different PWV values. These findings, obtained in patients at high cardiovascular risk, may be relevant when evaluating the prognostic importance of PWV.